2014
DOI: 10.3390/f5123131
|View full text |Cite
|
Sign up to set email alerts
|

Douglas-Fir Tussock Moth- and Douglas-Fir Beetle-Caused Mortality in a Ponderosa Pine/Douglas-Fir Forest in the Colorado Front Range, USA

Abstract: An outbreak of the Douglas-fir tussock moth, Orgyia pseudotsugata McDunnough, occurred in the South Platte River drainage on the Pike-San Isabel National Forest in the Colorado Front Range attacking Douglas-fir, Pseudotsuga menziesii (Mirb.) Franco. Stocking levels, species composition, and tree size in heavily and lightly defoliated stands were similar. Douglas-fir tussock moth defoliation resulted in significant Douglas-fir mortality in the heavily defoliated stands, leading to a change in dominance to ponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This supports the hypothesis of reduced vigor in defoliated trees facilitating secondary disturbance and suggests a mechanistic linkage between WSB and DFB. Our findings corroborate localized field studies that demonstrate that prior defoliation by the Douglas-fir tussock moth may lead to increases in DFB populations [49] and the colonization of heavily defoliated trees [50]. Notably, our data suggest that the effect of prior defoliation on subsequent DFB outbreaks persists at broad spatial scales, despite complex cross-scale interactions that characterize bark beetle outbreaks [30].…”
Section: Discussionsupporting
confidence: 85%
“…This supports the hypothesis of reduced vigor in defoliated trees facilitating secondary disturbance and suggests a mechanistic linkage between WSB and DFB. Our findings corroborate localized field studies that demonstrate that prior defoliation by the Douglas-fir tussock moth may lead to increases in DFB populations [49] and the colonization of heavily defoliated trees [50]. Notably, our data suggest that the effect of prior defoliation on subsequent DFB outbreaks persists at broad spatial scales, despite complex cross-scale interactions that characterize bark beetle outbreaks [30].…”
Section: Discussionsupporting
confidence: 85%
“…Trees experiencing reduced growth rates in recent years, perhaps due to stressors such as drought, have also been found to be more susceptible [12,21]. On a stand level, higher Douglas-fir basal area and higher overall stand density increased the odds of beetle infection [12,22,23], and landscape-level topographical features that create drier conditions, such as aspect, slope, and elevation, correlate with increased Douglas-fir beetle infestations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moth communities (Lepidoptera) are among the many taxa experiencing human-induced declines in many regions of the planet (Wagner et al 2021), with increased wildfire activity identified as one of the drivers of the process. In contrast, fire suppression in many forested ecosystems over the past century has led to increased tree densities and canopy closure, leading to shifts in relative abundance of many insect species, including increases of "pest" moth species Environmental Entomology, 52(4), 2023, 606-617 https://doi.org/10.1093/ee/nvad068 Advance Access Publication Date: 15 July 2023 Research (McCullogh et al 1998, Negrón et al 2014. Wildfires and other anthropogenic changes in climate have also contributed to globalscale increases in defoliator moth outbreaks in forests, in concert with increases in other forest insect pests and pathogens (Kautz et al 2016).…”
mentioning
confidence: 99%